Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12906-017-1810-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity activity, acute toxicity, and chemical constituents of aqueous and ethanol Viola mandshurica extracts

Abstract: Background Viola mandshurica has traditionally been used as an expectorant, diuretic, and anti-inflammatory drug. The present study was designed to test the hypothesis that low doses of two different V. mandshurica extracts have anti-obesity effects.MethodsWe evaluated the effects of ethanol extract (VME) and aqueous extract (VMA) from V. mandshurica on high-fat diet (HFD)-induced obese mice as well as the acute oral toxicities and chemical compositions of both extracts.ResultsOral administration of VME or VMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
3
14
0
Order By: Relevance
“…PPARγ serves a dominant function in the differentiation and maturation of adipocytes (36,37). Previous studies have identified that an HFD induces the expression of adipogenic genes such as those encoding PPARγ and c/EBPα (38)(39)(40). This was also true in the present study as mice fed on an HFD exhibited an increase in the expression of phosphorylated PPARγ and c/EBPα protein.…”
Section: Resultssupporting
confidence: 82%
“…PPARγ serves a dominant function in the differentiation and maturation of adipocytes (36,37). Previous studies have identified that an HFD induces the expression of adipogenic genes such as those encoding PPARγ and c/EBPα (38)(39)(40). This was also true in the present study as mice fed on an HFD exhibited an increase in the expression of phosphorylated PPARγ and c/EBPα protein.…”
Section: Resultssupporting
confidence: 82%
“…It serves a role in reducing appetite and increasing energy consumption (30,31). It has been reported that leptin levels in the serum are increased in HFD-induced obese mice (32,33), causing leptin resistance (34). In the present study, it was proven that DLE reduced serum leptin levels in HFD-induced obese mice.…”
Section: Discussionsupporting
confidence: 61%
“…The effect of fat cell-derived adiponectin on insulin-sensitizing and fatty acid-oxidizing action is dependent on AMPK in the adipose tissue and liver ( 67 ). In the present study, it was revealed that mRNA expression of AMPKα was decreased in the liver of HFD mice, which suggested that the alterations in AMPKα expression enhanced the pathogenesis of lipid accumulation in the livers of NAFLD HFD mice ( 46 ). However, BHe significantly and dose-dependently stimulated AMPK expression and inhibited ACC1 mRNA expression in the hepatic tissues (in a manner comparable with the effects of 250 mg/kg metformin), which suggested that BHe ameliorated abnormal lipid metabolism through the suppression of lipogenesis and the promotion of fatty acid oxidation via the upregulation of AMPK.…”
Section: Discussionmentioning
confidence: 53%
“…The mRNA expression of acetyl-CoA carboxylase 1 (ACC1), AMPKα1 and AMPKα2 in hepatic tissues, and mRNA expression of leptin, uncoupling protein 2 (UCP2), adiponectin, CCAAT/enhancer-binding protein (C/EBP)α, C/EBPβ and sterol-regulatory-element-binding protein 1c (SREBP1c) in periovarian adipose tissue were determined using RT-qPCR ( 46 ). Briefly, RNA from adipose tissues was isolated using TRIzol ® reagent (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA).…”
Section: Methodsmentioning
confidence: 99%